(untitled) (African Journal of Law and Politics, 2025)
Originality, the criterion for protecting creative works, has often been opposed to novelty, the criterion for protecting industrial creations. Beyond the conceptual disparity, the analysis of the relationships between the two notions reveals a similarity both on a theoretical and practical level, one being deduced from the other. To this end, the consecration of the concept of novelty by copyright, taken in that a creation is distinguished from its predecessors, will allow a transversal analysis of this condition of protection within the large group that is intellectual property and put an end to certain controversies.